Nanomedical research and development in Spain: improving the treatment of diseases from the nanoscale - Fernández-Gómez, Paula; Pérez de la Lastra Aranda, Carmen; Tosat-Bitrián, Carlota; Bueso de Barrio, Jesús Alejandro; Thompson, Sebastián; Sot, Begoña; Salas, Gorka; Somoza, Álvaro; Espinosa, Ana; Castellanos, Milagros; Palomo, Valle (Frontiers in Bioengineering and Biotechnology, 2023)
The new and unique possibilities that nanomaterials offer have greatly impacted biomedicine, from the treatment and diagnosis of diseases, to the specific and optimized delivery of therapeutic agents. Technological advances in the synthesis, characterization, standardization, and therapeutic performance of nanoparticles have enabled the approval of several nanomedicines and novel applications. Discoveries continue to rise exponentially in all disease areas, from cancer to neurodegenerative diseases. In Spain, there is a substantial net of researchers involved in the development of nanodiagnostics and nanomedicines. In this review, we summarize the state of the art of nanotechnology, focusing in nanoparticles, for the treatment of diseases in Spain (2017-2022), and give a perspective on the future trends and direction that nanomedicine research is taking.